2007
DOI: 10.1103/physrevb.76.172410
|View full text |Cite
|
Sign up to set email alerts
|

Effect of quantum tunneling on the ignition and propagation of magnetic avalanches inMn12acetate

Abstract: Using a wire heater to ignite magnetic avalanches in fixed magnetic field applied along the easy axis of single crystals of the molecular magnet Mn 12 acetate, we report fast local measurements of the temperature and time-resolved measurements of the local magnetization as a function of magnetic field. In addition to confirming maxima in the velocity of propagation, we find that avalanches trigger at a threshold temperature which exhibits pronounced minima at resonant magnetic fields, demonstrating that therma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
44
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(52 citation statements)
references
References 22 publications
7
44
1
Order By: Relevance
“…3 is due to the 22 kOe field applied each time before the avalanche was ignited.͒ There is a clear correlation between the two: The initial relaxation reduces "flammability" of the crystal. These results are similar to the results on molecular magnets 24,27 and on manganites. 25 In order to distinguish between the temperature rise due to the heat pulse itself and the temperature rise due to the avalanche we plotted Fig.…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…3 is due to the 22 kOe field applied each time before the avalanche was ignited.͒ There is a clear correlation between the two: The initial relaxation reduces "flammability" of the crystal. These results are similar to the results on molecular magnets 24,27 and on manganites. 25 In order to distinguish between the temperature rise due to the heat pulse itself and the temperature rise due to the avalanche we plotted Fig.…”
Section: Resultssupporting
confidence: 81%
“…This process is driven by the heat conductance and it closely resembles the magnetic deflagration observed in molecular magnets and manganites. [22][23][24][25][26][27][28][29] The dependence of avalanches on the initial state, initial temperature, and magnetic field agrees with the theory of deflagration. 30 Since magnetic transition in Gd 5 Ge 4 also involves structural transformation, it represents an interesting example of the magnetostructural deflagration.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…McHugh et al [22] used a resistive wire element as a simple electric heater to trigger avalanches in a manner similar to the work of Paulsen and Park [1]. In these experiments, an external magnetic field is ramped to, and held at a fixed value.…”
Section: Avalanche Ignitionmentioning
confidence: 99%
“…Additionally, it has been also shown that the required temperature to ignite avalanche at particular values of the longitudinal field, h z , presents dips at resonant fields. 10 In this Brief Report we study the deflagration threshold in Mn 12 -Ac in a magnetic field applied at an angle with respect to the anisotropy axis. In a first approximation the magnetic Hamiltonian of the crystal is…”
mentioning
confidence: 99%